2020
DOI: 10.18632/aging.202308
|View full text |Cite
|
Sign up to set email alerts
|

MiR-16-5p suppresses myofibroblast activation in systemic sclerosis by inhibiting NOTCH signaling

Abstract: Systemic sclerosis (SSc) is a prototypic fibrotic disease characterized by localized or diffuse skin thickening and fibrosis. Tissue fibrosis is driven by myofibroblasts, and factors affecting myofibroblast activation may also be involved in the development of SSc. In this study, we examined molecular mechanisms underlying SSc by focusing on myofibroblast activation processes. Bioinformatics analysis conducted to identify differentially expressed miRNAs (DEMs) and genes (DEGs) revealed that microRNA-16-5p (miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Manesh et al [56] found that miR-16 may affect the important pathogenic events of systemic sclerosis by targeting the nuclear proteins survivin and p53 that control cell cycle and apoptosis, inhibiting endothelial cell proliferation and promoting apoptosis. Similarly, it has been found that miR-16-5p can directly bind Smad3 [22] and Notch2 [26] to inhibit the activation and phenotypic transformation of fibroblasts and reduce the synthesis of collagen and other ECM and α-Smooth muscle actin(α-SMA) expressions, indicating that it has a direct anti-fibrotic effect.…”
Section: Other Fibrotic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Manesh et al [56] found that miR-16 may affect the important pathogenic events of systemic sclerosis by targeting the nuclear proteins survivin and p53 that control cell cycle and apoptosis, inhibiting endothelial cell proliferation and promoting apoptosis. Similarly, it has been found that miR-16-5p can directly bind Smad3 [22] and Notch2 [26] to inhibit the activation and phenotypic transformation of fibroblasts and reduce the synthesis of collagen and other ECM and α-Smooth muscle actin(α-SMA) expressions, indicating that it has a direct anti-fibrotic effect.…”
Section: Other Fibrotic Diseasesmentioning
confidence: 99%
“…In addition, miR-15a and miR-16 can also affect other signaling pathways related to ECM formation. Yao et al [26] found that miR-16-5p inhibited the activation of the Notch signaling pathway by targeting Notch2, thereby increasing the expression of MMP-1 and MMP-8 in human skin fibroblasts and promoting the degradation of collagen and other ECM components. Chen et al [27] found that the overexpression of miR-15a inhibited Yesassociated protein (YAP1), a key effector molecule in the Hippo pathway, and affected the activation of the downstream signal YAP1/TEAD/Twist, thereby inhibiting the synthesis of collagen and other ECM components in lung fibroblasts.…”
Section: Regulation Of the Synthesis And Degradation Of Ecmmentioning
confidence: 99%
“…This miRNA has been shown to suppress breast cancer proliferation [ 125 ]. Another study demonstrated that miR-16-5p has an inhibiting role in the Notch signaling pathway [ 126 ]. Therefore, it could be a diagnostic and prognostic potential biomarker in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs also exert epigenetic regulation on fibroblasts. Low level of miR-16–5p activates fibrosis by positively regulating the NOTCH signaling [ 144 ]. In addition, miR33a-3p can downregulate level of DKK-1, an antagonist of Wnt pathway, and promote the fibrosis [ 145 ].…”
Section: Systemtic Sclerosismentioning
confidence: 99%